“But Someone Has to Shout”: Henrikas Nagys’s Polemical Position in Literatūros Lankai - Žvirgždas, Manfredas (Colloquia, 2025)
The article relates to the position of Henrikas Nagys in the formation process of Lithuanian journal Literatūros lankai (Literary Folios, 1952–1959), analysing his impact to the aesthetical preferences of co-authors. In Nagys’ creative imagination, the literary field was constructed as a scene “where the drama of us (and of those who resemble us) had been acted” (Vytautas Kavolis). Nagys declared that the most important features of a good literary work were originality of the author and fidelity to artistic truth. Critical reviews and interviews by Nagys are taken into account, as well as his correspondence with colleagues.